High Prevalence of Post-Transplant Donor Specific HLA-DQ Antibody in Live Related Renal Transplantation. (July 2018) - Zafar, Mirza Naqi; Musharraf, Wajiha; Abbas, Khawar; Ashraf, Sabra; Rizvi, Adibul Hasan
Abstract : Purpose: The aim of this study was to determine the HLA classes of post-transplant donor specific antibody (DSA) in live related renal transplant recipient. Patients and Method: HLA antibodies were analyzed in 212 renal transplant recipient, <3 to 36 months post-transplant. Samples were collected in routine follow-up in out-patient clinic. All recipients had stable graft function in the last 6 months. HLA antibody was negative by flow cross match and Luminex pre-transplant. All rejections were confirmed by biopsy. Antibody screen and single antigen screen was undertaken by Luminex. Outcomes were compared between recipient with DSA and No DSA for rejection, HLA match, Serum Creatinine and Graft Survival. Results: Of the 212 recipient screened for HLA antibodies 20 (9.4%) were positive for Class I and 34 (16%) for Class II. DSA were found in 31 (14.6%). DSA developed in 2 (7%) of the recipient within 3 months, in 4 (14%) within 6 and 25 (79%) after 6 months. DSA against Class I in 10 (4.7%) and Class II in 27 (13%). Within Class I, against HLA A in 9 (90%) and HLA B 1 (10%), while within Class II, HLA-DR in 11 (41%), HLA-DQ in 15 (55%) and HLA-DR + HLA-DQ in 1 (3.7%). Rejections were diagnosed in 16 (52%) of DSA group vs 48 (26%) in No DSA group (p< 0.05). The mean HLA match was 3.39 ± 0.9 in DSA vs 3.67 ± 1.2 in Non DSA (p 0.231). The mean S. Creatinine was 2.42 ± 1.4 mg/dl in DSA vs 1.6 ± 0.8 in Non DSA (p 0.001). Graft survival in DSA group at 1 and 5 years was 100%, 71% vs 100% and 94% in the No DSA group, (p< 0.009). Conclusion: In OPD follow-up 14.6% of the recipient had DSA mainly against Class II HLA-DQ antigens. Rejection episodes were higher in patients with DSA and graft survival was poorer as compared to Non DSA group. High frequency of HLA-DQ antibodies warrant typing for HLA-DQ as routine specially in live related transplant to determine the long term consequences of DSA against HLA-DQ antigens and their management.